Understanding the nature and determinants of store loyalty in China - Song, Aijing (2021)
Store loyalty is confirmed to be important for retailers as it can help them gain and retain a competitive advantage over their counterparts. Researchers suggest that to achieve store loyalty the retailer needs to cope with competition from both the task environment and the institutional environment. The task environment may require the retailer to provide merchandise of good quality and price and with a broad range of choice. In the institutional environment, consumers may develop diversified requirements towards a specific store where they conduct their shopping because they have diversified roles in society, e.g., as an employee, a member of the community, and/or as a religious believer. To meet challenges from the institutional environment, a store may donate to the community or ensure a good working environment for employees. According to institutional theory, once these rules are followed consumers perceive the store to be legitimate in the current institutional environment. This is referred as organizational legitimacy. Therefore, it is suggested that the consumers will support the store. This argument builds a solid foundation for the current research. It signifies the importance of institutional environment for establishing store loyalty.